Evidence Legitimacy of Intern Certification Before Primary Consideration in Law Issuance by Judge Within Private Dispute - Ruslin Ruslin (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2020)
A Custom in society about completing Transaction deals or agreements are confirmed in many ways (oral, written or noted) and somehow proved with piece of paper (Receipt) for transaction as receiver accepts goods or services without cordage of notary / Property officials, in verse 5, act number 5 1960 about Essences of Agriculture determines that; “Agriculture Law upon lands, water, and air are customized act unless limited within nation affair ……. etc,Supreme Court Jurisprudence Number 126K/Sip/1973, dated May Fourth 1976 which stated that ; “ The Legitimacy of Property Purchasing is not merely absolute confirmed in supervision of Property officials “, read also Supreme Court Jurisprudence Number 665K/Sip/1979, dated July twenty second 1980, as follows : “ as The Transaction occurred between Marketer and Customer supervised by authorized chief attended by two witnesses and cost is accepted by the marketer, therefore the purchasing is absolutely legal before the law even not committed in a supervision of Property Officialls. It is alike to Surabaya State Court Issuance Number: 451/Pdt.G/2008/PN.Sby, dated April seventh 2009 with fixed Law Issuance states; “Property transaction is legal as long as completing conditions of act 1320 BW”. Judge Law Consideration about Supremacy or value of Intern Certificate Evidence for one private case among others are frequently occurred in Legitimacy of Internal Certification, therefore there are Evidence Isuance Misperceptions about its supremacy by some Judges (as Supreme Court Issuance Number. 537K/Pdt/1985, but there are some Judge Considerations confirmed as Internal Certification is renowned verification it equals to authentic one (as confirmed by Issuance of Supreme Court number. 4434K/Pdt/1986). However, any Judges stated as the evidence for the certification is created as a primary written record (Stated by Supreme Court Issuance Number. 167K/PDT). Keywords: legitimacy; intern certification; signature legitimacy